Whitish Patch over Soft Palate: A Case Report of Incidental Finding of Basaloid Squamous Cell Carcinoma - Jeeven Velayutham; Jeyasakthy Saniasiaya; Mohd. Zulkiflee Bin Abu Bakar (Talenta Publisher, 2023)
Background: Whitish lesion over the oropharyngeal mucosal lesion is traditionally attributed to benign lesions such as leukoplakia, oral candidiasis or lichen planus, which can be diagnosed through histopathological examination. Yet, performing a biopsy is prudent in all cases of persistent whitish lesions to rule out a more sinister pathology such as malignancy. Objective: To report an incidental finding of a whitish lesion in the soft palate of a gentleman who presented with otalgia and otorrhea, which turned out to be basaloid squamous cell carcinoma (BSCC). Methods: We performed a thorough examination in a patient presenting with ear symptoms, during which a whitish palatal lesion was incidentally discovered. Histopathological examination was carried out to confirm the diagnosis. Results: Histopathological analysis revealed that the whitish palatal lesion was basaloid squamous cell carcinoma (BSCC). Conclusion: Thorough, meticulous, and complete Ear, Nose and Throat examinations in all patients are crucial, as they enable early diagnosis of sinister pathologies, such as BSCC, even when presenting symptoms seem unrelated.